The Diagnostics and Management of Bronchopulmonary Sequestration: An International Survey among Specialized Caregivers - Kersten, C.M.; Jansen, M.D.G.; Zuidweg, M.J.P.; Wijnen, R.M.W.H.; Krasemann, T.B.; Schnater, J.M. (European Journal of Pediatric Surgery, 2024)
Background Our objective was to explore the treatment preferences for bronchopulmonary sequestration (BPS) among an international group of specialized caregivers.Methods Sixty-three participants from 17 countries completed an online survey concerning the diagnostics, treatment, and follow-up. Recruitment took place among members of the Collaborative Neonatal Network for the first European Congenital Pulmonary Airway Malformation Trial Consortium and through the Association for European Pediatric and Congenital Cardiology working group database.Results Most of the 63 participants were pediatric surgeons (52%), followed by pediatric pulmonologists (22%), and pediatric cardiologists (19%). The majority (65%) treated more than five cases per year and 52% standardly discussed treatment in a multidisciplinary team. Half of the participants (52%) based the management on the presence of symptoms, versus 32% on the intralobar or extralobar lesion localization. Centers with both surgical and interventional cardiac/radiological facilities (85%) preferred resection to embolization in symptomatic cases (62 vs. 15%). In asymptomatic cases too, resection was preferred over embolization (38 vs. 9%); 32% preferred noninterventional treatment, while 11% varied in preference. These treatment preferences were significantly different between surgeons and nonsurgeons (p < 0.05). Little agreement was observed in the preferred timing of intervention as also for the duration of follow-up.Conclusions This survey demonstrates a variation in management strategies of BPS, reflecting different specialist expertise. Most centers treat only a handful of cases per year and follow-up is not standardized. Therefore, management discussion within a multidisciplinary team is recommended. Recording patient data in an international registry for the comparison of management strategies and outcomes could support the development of future guidelines.Level of Evidence: Level IV.
Keywords: congenital lung abnormalities; bronchopulmonary sequestration; surgery; surgical resection; embolization; survey